Peran Pengajian Halaqah Terhadap Peningkatan Pengetahuan Nahwu Santri Di Pondok Pesantren Al-Urwatul Wutsqaa - Zaitun Zaitun; Hasmulyadi Hasmulyadi (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
This research discusses the role of halaqah recitation in increasing nahwu knowledge of students at Al-Urwatul Wutsqaa Islamic Boarding School, Benteng Village, Sidrap Regency. The main problem being studied is the implementation of the halaqah recitation, the nahwu knowledge of students and the supporting and inhibiting factors of increasing the nahwu knowledge of students. This study aims to determine the process of implementing halaqah recitation, increasing nahwu knowledge, as well as supporting and inhibiting factors for increasing students' nahwu knowledge. This research is a qualitative descriptive study with an educational approach and a psychological approach. This type of this research is field research. Data collection techniques in this research using observation, interviews, and documentation. The results of this study indicate that the recitation of halaqah at Al-Urwatul Wutsqaa Islamic Boarding School plays an important role in increasing the knowledge of nahwu students. It is seen that students already know the position of words and are able to give vowels to every word contained in the book. Supporting factors for increasing nahwu knowledge with learning other than halaqah recitation, such as Arabic takhassus, Musabaqah Qira'atul Kutub, Arabic language villages and other extracurricular programs and books studied in halaqah recitation were tested on even and odd semester examinations. The inhibiting factor is from the lack of interest of some students, so they are less motivated in following the halaqah recitation process.